1978
DOI: 10.1111/j.1600-0722.1978.tb00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental maturity in hypopituitarism, and dental response to substitution treatment

Abstract: In 25 patients with hypopituitarism the relation of skeletal and dental maturity and the effects on it of substitution therapy for 2-4 years were analyzed. Dental age was retarded less regularly and to a lesser degree than skeletal age and statural growth. In most patients dental age was within the range of 0-2 s.d. All components of dental development seemed equally retarded. Changes in dental delay during GH treatment were variable, but in most cases parallel to the changes in statural and skeletal delay. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…This study also indicated that there was little difference in the development of the teeth following 6–12 months of treatment with growth hormone replacement therapy, the average delay in dental age represented 65% of the skeletal age. In contrast to the findings by Keller et al [6], Myllärniemi et al [16] in a study involving 25 patients with GHD noted that hypopituitarism caused less delay in tooth development than in skeletal development, but development in dental maturation was speeded up with replacement hormone therapy.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This study also indicated that there was little difference in the development of the teeth following 6–12 months of treatment with growth hormone replacement therapy, the average delay in dental age represented 65% of the skeletal age. In contrast to the findings by Keller et al [6], Myllärniemi et al [16] in a study involving 25 patients with GHD noted that hypopituitarism caused less delay in tooth development than in skeletal development, but development in dental maturation was speeded up with replacement hormone therapy.…”
Section: Discussionmentioning
confidence: 62%
“…The effect of GH in dental development is not well understood, although it appears that development is retarded in the case of GHD [6,10–14]. When this deficit is treated the situation may either return to normal and dental age become almost equal to chronological age [12], or dental age may only improve slightly [15,16]. The aim of this study was to relate dental age and bone age to chronological age in a group of children with GHD.…”
Section: Introductionmentioning
confidence: 99%
“…This would explain the finding of delayed dental age in many of the patients in our present study. Dental development was also found to be delayed in idiopathic short stature, but dental development accelerated with time [Ito et al, 19931. The effect of GH treatment on dental age is still unclear [Myllarniemi et al, 1978a;Ito et al, 19931.…”
Section: Discussionmentioning
confidence: 99%
“…Children with GH deficiency exhibit signs such as short stature, changes in orofacial development, and retarded dental maturity (10)(11)(12)(13). Most of the studies on dental maturity in children with GH-deficiency have been performed with small groups of post-pubertal children with different medical diagnoses.…”
mentioning
confidence: 99%